Determinants Non-Performing Financing (NPF) in Indonesia (Equilibrium: Jurnal Ekonomi Syariah, 2020)
This study aims to analyze the significance effect of Minimum Capital Requirement (KPMM), Financing to Deposit Ratio (FDR), Operating Expenses to Operations Revenue (BOPO), and Gross Domestic Product (GDP) toward Non-Performing financing (NPF) at Sharia Commercial Banks in Indonesia. This study uses analysis multiple linear regression (PLS) method. The sample in this study is the quarterly Sharia Commercial Banks (BUS) in the period of 2014-2019. The result of this study showed that KPMM, FDR, BOPO, and GDP simultaneously have a significant effect toward NPF. Partially KPMM, FDR, and BOPO have a significant effect toward NPF, and GDP partially not significant effect toward NPF in Indonesia Sharia Commercial Banks period 2014-2019.